Optimum Time Compression in Project Scheduling - Lamberson, L. R.; Hocking, R. R. (Management Science, 1970)
An algorithm based on convex programming is developed for optimum time compression in network scheduling systems. The development allows for the activity time-cost trade-off functions to be any differentiable convex function. Decomposition theory is then applied to reduce the amount of computation necessary. This along with a limited number of rules to structure any incoming vector makes the algorithm amenable to time compression in large project networks.